Health consequences of child removal among Indigenous and non‐Indigenous sex workers: Examining trajectories, mechanisms and resiliencies. Issue 8 (1st September 2021) - Kenny, Kathleen S.; Krüsi, Andrea; Barrington, Clare; Ranville, Flo; Green, Sherri L.; Bingham, Brittany; Abrahams, Ronald; Shannon, Kate
Abstract: The child protection system can be a highly consequential institution for mothers who are sex workers, yet scant attention has been paid to the health consequences of its policies on this population. Drawing on 31 in‐depth, semi‐structured interviews with 19 Indigenous and 12 non‐Indigenous sex workers in Vancouver, Canada, and using the stress process model and the concept of slow violence, this study proposes a typology of four trajectories through which child removal by this system shaped sex workers' health. Results suggest that child removal has health consequences beyond the conventionally thought of mechanism of mental distress and related health sequelae, to additionally alter women's social conditions, which also carried risks for health. Notably, while trajectories of Indigenous and non‐Indigenous sex workers were similar, Indigenous participants, whose families are disproportionately impacted by long‐standing colonial policies of child removal, were more severely jeopardized. Findings highlight how child removal can enact violence in the form of reverberating harms to sex workers' health, further reinforcing their marginalized statuses. This study calls for greater attention to how the child protection system (CPS) may influence the health of marginalized mothers, including how health inequities may be both causes and consequences of interventions by this system.